A review of halide charge carriers for rocking‐chair and dual‐ion batteries. Issue 4 (7th May 2021) - Sandstrom, Sean K.; Chen, Xin; Ji, Xiulei
Abstract: This review discusses how halide ion species have been used as charge carriers in both anion rocking‐chair and dual‐ion battery (DIB) systems. The anion rocking‐chair batteries based on fluoride and chloride have emerged over the past decade and are garnering increased research interest due to their large theoretical energy density values and the natural abundance of halide‐containing materials. Moreover, DIBs that use halide species as their anionic charge carrier are seen as one of the promising next‐generation battery technologies due to their low cost and high working potentials. Although numerous polyatomic anions have been studied as charge carriers, the use of single halide ions (i.e., F − and Cl − ) and metal‐based superhalides (e.g., [MgCl3 ] − ) as anionic charge carriers in DIBs has been considerably less explored. Herein, we provide an overview of some of the key advances and recent progress that has been made with regard to halide ion charge carriers in electrochemical energy storage. We offer our perspectives on the current state of the field and provide a roadmap in hopes that it helps researchers toward making new advances in these promising and emerging areas. Abstract : The study of halide species as charge carriers has emerged in recent years as an interesting alternative to the more traditional cation shuttles. Halide ion species have been explored as charge carriers for a variety of battery operation mechanisms, including anion rocking‐chair batteries (i.e., halide ion batteries) and (reverse) dual‐ion batteries. Here, we present a summary and analysis of how single halide ions (i.e., F − and Cl − ) and metal–halide complex ions (i.e., metal‐based superhalides) have been used as charge carriers in rechargeable battery systems. A roadmap of future research directions is also provided to help encourage and guide researchers in making new advances in this exciting and burgeoning field.